Implementation Of PSAK 202 In The Presentation And Disclosure Of PT Unilever Indonesia's Financial Statements For The 2020-2024 Financial Years: A Literature Review - Sri Devi; Dicky Siddik Permana; Donni Afrianto; Wiwik Pratiwi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Study This aiming For review theory and implementation Statement Standard Accountancy Finance (PSAK) 202 on supplies , as well as evaluate its application to the report finances of PT Unilever Indonesia Tbk during period 2020–2024. PSAK 202, which refers to the standard international IFRS, providing guidelines about classification , determination cost acquisition , method recording , measurement mark realization clean , decrease value , up to disclosure supply in report finance . With use approach quantitative and qualitative as well as based on theory accountancy positive and normative , research This highlight implementation weighted average method in recording cost acquisition inventory by PT Unilever Indonesia Tbk . The results of the analysis show that company has comply provisions of PSAK 202 in particular consistent , including in confession burden inventory , adjustment provision on supply obsolete , and presentation inventory at value realization clean . Proper implementation of PSAK 202 rated contribute to transparency , accuracy and credibility report finance company .